Deficits and the dollar : the world economy at risk - Marris, Stephen (Washington, D.C. : Institute for International Economics, 1985)
This book is unique, it reveals the perspective and experiences of nearly thirty years at the organization for Economic cooperation and Development in Paris.
Bibliography: p. 335-343.
asm; 25/01/19
Loans
Keywords: Budget deficits; Dollar, American; Balance of payments; Saving and investment